2018
DOI: 10.1093/icvts/ivy103
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic port access surgery for isolated atrioventricular valve endocarditis†

Abstract: Complex atrioventricular valve surgery in the context of AVVE can be endoscopically performed in experienced centres and should not deter surgeons from offering patients with AVVE the potential benefits of minimally invasive cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Of note, one of the included studies included 6 patients (out of 66 total) with isolated tricuspid valve endocarditis. 10 The average in-hospital mortality was 9.4%, with average length of hospital stay of 21.6 days. Survival was 89.1% at 30 days and 79.3% at or above 1 year.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Of note, one of the included studies included 6 patients (out of 66 total) with isolated tricuspid valve endocarditis. 10 The average in-hospital mortality was 9.4%, with average length of hospital stay of 21.6 days. Survival was 89.1% at 30 days and 79.3% at or above 1 year.…”
Section: Resultsmentioning
confidence: 94%
“…We identified 6 reports (5 case series without comparison groups and 1 cohort study comparing against median sternotomy) involving a total of 271 patients. 9 -14 The patients had mean age 60.4 ± 14.9 years and 60.1% were male. Mean EuroSCORE II was 24.6 ± 23.2 in studies that reported values.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of MIAS conversion to CSA due to adverse intraoperative events ranges considerably, with experienced centres reporting an incidence of 3.0% (64) -3.7%. (17) The group from Aalst suggested an increased mortality associated with conversion during PAS (64) and also reported their individual conversion rates in the context of complex isolated AVV endocarditis (9.1%), (74) redo-PAS after previous PAS (19.2%), (75) difficult access congenital chest wall deformities (0%), (76) extreme obesity (0%), (77) post-cardiac transplantation (0%) (78) and hypertrophic obstructive cardiomyopathy with associated AVV disease (0%).…”
Section: Conversion To Classic Sternotomy Due To Adverse Mias Events and Its Impact On Clinical Outcomementioning
confidence: 99%
“…(89)(90)(91)(92) However, in-hospital stabilisation of anti-coagulation regimes and completion of a 6-week antibiotic course in cases of infective endocarditis, does not reflect the isolated impact on hospitalisation of MIAS. (74)(75)(76)(77)(78) In-hospital mortality Contemporary reports do not suggest a significant all-cause inhospital mortality difference between MIAS and CSA (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63) or EBAO and DAC. (70)(71)(72)(73) The group from Aalst reported a perioperative mortality of 2.6% for their PAS series.…”
Section: Duration Of Hospital Staymentioning
confidence: 99%
See 1 more Smart Citation